The study of taxonomy and systematics enhances ecological and conservation science - Rowden, Ashley (New Zealand Science Review, 2016)
​The study of taxonomy and systematics can enhance ecological and conservation science. However, understanding how taxonomy and systematics can bring about such enhancement is not always readily appreciated. This situation can lead to some ecologists ignoring or dismissing the benefits of working with taxonomists and systematists to achieve their goals. Here I provide examples, from collaborative research with marine bryozoologist Dennis Gordon, on how his understanding of taxonomy and systematics has enabled insights into the regeneration of biogenic reef habitat impacted by fishing, the factors that influence the distribution of bryozoan assemblages and thickets in the New Zealand region, and where they require protection.